Distinct Effects of Short Chain Fatty Acids on Host Energy Balance and Fuel Homeostasis With Focus on Route of Administration and Host Species - Kong, Dehuang; Schipper, Lidewij; van Dijk, Gertjan (Frontiers in Neuroscience, 2021)
Accumulating evidence implicates gut-microbiota-derived metabolites as important regulators of host energy balance and fuel homeostasis, the underlying mechanisms are currently subject to intense research. In this review, the most important executors, short chain fatty acids, which both directly and indirectly fulfill the interactions between gut microbiota and host will be discussed. Distinct roles of individual short chain fatty acids and the different effects they exert on host metabolism have long been overlooked, which compromises the process of clarifying the sophisticated crosstalk between gut microbiota and its host. Moreover, recent findings suggest that exogenously administered short chain fatty acids affect host metabolism via different mechanisms depending on the routes they enter the host. Although these exogenous routes are often artificial, they may help to comprehend the roles of the short-chain-fatty-acid mechanisms and signaling sites, that would normally occur after intestinal absorption of short chain fatty acids. Cautions should be addressed of generalizing findings, since different results have appeared in different host species, which may imply a host species-specific response to short chain fatty acids.